STUDENT CONTRIBUTION INDEX (SCI) IN SCIENCE: A MEASURE OF CONTRIBUTION TO MITIGATING SOCIAL LOAFING AND FREE-RIDING IN TEAM PROJECTS - Yasin, Burhanuddin; Burhan, Omar K; Mustafa, Faisal; Fata, Ika Apriani; Komariah, Endang (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
In this study, we introduce the Student Contribution Index (SCI) to measure these contributions. The purpose of this quantitative study is to test the validity of SCI as a measure of task identifiability and to determine the student satisfaction with SCI-based assessments. To collect the data, 52 students were split into high and low identifiability conditions. Both groups worked on a project and completed SCI once (LI group) and twice (HI group). We measured the SCI variability using an F-test at the significance level of 0.05. Furthermore, a group project of 113 students was assessed using SCI. Students completed an evaluation form to measure procedural fairness, distributive fairness, and satisfaction. We then analyzed the correlations between these variables using Pearson's Correlation. The results show that the variability in SCI of the HI group was negligible (SD = 0), indicating that all students contributed equally to the project. Meanwhile, a variability was observed in the LI condition (SD = 0.08), suggesting that SCI was a valid measurement. Additionally, students were generally satisfied with the assessment (M = 4.40), and a significant correlation was observed between the variables. This study presents a novel method for assigning grades to group members in group projects, taking into account each member’s individual contribution. As a result, fairness in grading can be achieved, and educators can discourage social loafing and free-reading behavior.